Dynamic Scheduling For Short-Life Span Construction Projects In Indian Smes: A Simulation-Based Study - Dangade, Sampada; Shiyekar, Sandeep; Patil, Ashwini (Journal of Neonatal Surgery, 2025)
The construction sector in India, especially among small and medium-sized businesses (SMEs), is critical to the country's economical progress. However, these SMEs often face the challenges of managing short-term projects with tight deadlines, restricted budgets, and changing resource availability. Traditional scheduling approaches, such as Gantt charts and the Critical Path Method (CPM), usually fall short of addressing these projects' dynamic and unpredictable character, resulting in inefficiencies, delays, and cost overruns. This study seeks to investigate the possibility of dynamic scheduling as an adaptable strategy that allows for real-time alterations to project plans in response to changing circumstances. The research creates a dynamic short project scheduling framework designed for short-term construction projects in Indian SMEs using simulation-based approaches. The study uses simulation methodologies to investigate the effects of dynamic scheduling on key performance metrics such as time management, cost efficiency, and resource utilisation. The research delivers practical insights that might improve project management techniques in the SME construction industry by comparing the results of dynamic scheduling to traditional approaches. The findings show that dynamic scheduling enhances project performance considerably by allowing project managers to reallocate resources, change schedules, and react quickly to unexpected occurrences. Furthermore, the study emphasises the importance of increasing SMEs' understanding and technical skills in order to promote the implementation of current scheduling technology. This research addresses a key vacuum in the current literature and provides practical solutions that construction SMEs can easily apply, resulting in increased operational efficiency and market competitiveness.